Automated Guided Vehicle Systems A Primer with Practical Applications - Ullrich, Günter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This primer is directed at experts and practitioners in intralogistics who are concerned with optimizing material flows. The presentation is comprehensive covering both, practical and theoretical aspects with a moderate degree of specialization, using clear and concise language. Areas of operation as well as technical standards of all relevant components and functions are described. Recent developments in technology and in the markets are taken into account. The goal of this book is to further stronger use of automated guided transport systems and the enhancement of their future performance.
The History of Automated Guided Vehicle Systems -- Modern Areas of Application -- Technological Standards -- The Fourth Era -- Interdisciplinary Design of Automated guided Vehicle systems (AGVS).
Keywords: Engineering economics; Engineering economy; Robotics; Automation; Production management; Engineering Economics, Organization, Logistics, Marketing; Robotics and Automation; Operations Management